Image authentication system using deep learning / Muhammad Faisal Amer Faudzli and Muhamad Arif Hashim - Faudzli, Muhammad Faisal Amer; Hashim, Muhamad Arif (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Using a variety of techniques, image manipulation can be performed not only by commercial editors, but also by criminals and counterfeiters for the goal of counterfeiting. Digital forensic tools are required to detect the manipulation and tampering of images for such unlawful activities. For these reasons, this research offered an algorithm for detecting image manipulation using Convolutional Neural Network (CNN) technique that has produced excellent results in recent studies. In addition, the other purpose was to assess the performance of the developed CNN image authentication system in detecting tampering in images.